Enhanced photovoltaic performance of meso-porous SnO2 based solar cells utilizing 2D MgO nanosheets sensitized by a metal-free carbazole derivative1. Issue 8 (28th February 2015) - Qureshi, Mohammad; Chetia, Tridip Ranjan; Ansari, Mohammad Shaad; Soni, Saurabh S.
<x xml:space="preserve">Abstract</x> Herein, we report a power conversion efficiency of 3.71% using mesoporous SnO2 in combination with 2D MgO nanosheets, sensitized by a metal free carbazole dye.